Implementasi Hak Imunitas Ombudsman Terhadap Usaha Franchisee - Hartati, Nara; Hadi, Syamsul; Abdullah, Syifa (Justicia Insight, 2024)
This study aims to analyze the implementation of the immunity rights possessed by the Ombudsman in handling reports related to franchisee businesses and their impact on legal protection for the involved parties. The Ombudsman, as a public service supervisory institution, plays a strategic role in ensuring justice and accountability in the business sector, including franchisees. The immunity rights attached to the Ombudsman provide legal protection in carrying out its duties independently, but their implementation often faces challenges, particularly in cases involving business interests. The research employs a normative-juridical approach, analyzing laws and regulations, case studies, and interviews with relevant stakeholders. The findings indicate that the Ombudsman's immunity rights have been adequately implemented, although challenges remain, such as the franchisees' lack of understanding of the Ombudsman's functions and authority. This study recommends enhancing legal education for business actors and strengthening supervisory mechanisms to prevent potential abuse of immunity rights.